An applied analysis of ACE and CBIT reforms in the EU. - Mooij, R; Devereux, M (Springer Netherlands, 2010)
We assess the quantitative impact of two reforms to corporation tax, which would eliminate the differential treatment of debt and equity: the allowance for corporate equity (ACE) and the comprehensive business income tax (CBIT).We explore the impact of these reforms on various decision margins, using an applied general equilibrium model for the EU calibrated with recent empirical estimates of elasticities. The results suggest that, if governments adjust statutory corporate tax rates to balance their budget, profit shifting and discrete location render CBIT more attractive for most individual European countries. European coordination makes a joint ACE more, and a joint CBIT less efficient. A combination of ACE and CBIT is always welfare improving.